Adverbia Penanda Aspek dalam Novel Sansai karya Ermanto: Suatu Kajian Morfologi - Andayani, Zri; Liusti, Siti Ainim; Zulfariati, Zulfariati (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
This study examines the use of adverbial aspect markers in Ermanto's novel Sansai, aiming to revitalize Minangkabau literature by focusing on both cultural and social issues. The research explores how aspect markers influence narrative understanding and temporal dynamics in contemporary Minangkabau prose. Through qualitative document analysis using the Indonesian Language Corpus Linguistic Method (KORTARA), the study identifies and classifies adverbs that denote actions, events, situations, and traits in various temporal contexts. The analysis reveals four types of aspect markers: durative, perfective, imperfective, and inchoative. The novel contains 476 adverbial aspect markers, distributed as follows: 73 durative (